Experimental study of flush end plate beam-to-column composite joints with precast slabs and deconstructable bolted shear connectors. (August 2016) - Ataei, Abdolreza; Bradford, Mark A.; Liu, Xinpei
Abstract: Composite steel-concrete floor systems represent a ubiquitous structural steel framing system for commercial and industrial buildings in the developed world, which exploit the strengths of reinforced concrete and structural steel both symbiotically and in a complementary fashion. However, as attention is being focused increasingly towards minimising emissions and maximising recycling, these composite systems are problematic for many reasons. This paper describes the results of tests on three full-scale sustainable flush end plate semi-rigid beam-to-column joints and three push-out tests with deconstructable tensioned bolted shear connectors, needed to establish the strength of the shear connection in order to design the joints. For this system, precast concrete slabs having a reduced content of ordinary Portland cement are attached compositely to the steel beam using post-tensioned high-strength friction-grip bolts that are unbolted readily at the life-cycle end of the building. This innovative connection system is proposed to circumvent the high-carbon attributes associated with the demolition of conventional steel-concrete composite framing systems. The push-out tests show that the behaviour of specimens with post-installed bolts in clearance holes is significantly different to that of members with stud shear connectors in slabs cast in situ, and the bolted connectors provide reliable and adequate shear connection to composite beams and joints with precast concrete slabs. The test results show that these composite joints have credible rotation and moment capacities within the recommendations of EC3 and EC4, and that fracture of the joint occurs after substantial rotational deformations had been achieved.